2018
DOI: 10.1097/icb.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Serous Macular Detachment in a Patient With Nephrotic Syndrome

Abstract: In nephrotic syndrome cases especially with accompaniment of high blood pressure, fluid accumulation in the retina layer may occur. Serous macular detachment must be kept in mind when treating these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…These alterations would lead to secondary retinal pigment epithelium (RPE) dysfunction accounting for subretinal detachments and impaired photoreceptor outer segment phagocytosis leading to hyperautofluorescent subretinal material accumulation. The nephrotic syndrome could also have a role in the choroidal changes and subretinal detachments through a modification of the oncotic pressure [12,[17][18][19]. By restoring the plasmatic protein balance and decreasing amyloid deposits, the initiation of the first chemotherapy cycles led to the healing of the nephrotic syndrome and the resorption of the subretinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations would lead to secondary retinal pigment epithelium (RPE) dysfunction accounting for subretinal detachments and impaired photoreceptor outer segment phagocytosis leading to hyperautofluorescent subretinal material accumulation. The nephrotic syndrome could also have a role in the choroidal changes and subretinal detachments through a modification of the oncotic pressure [12,[17][18][19]. By restoring the plasmatic protein balance and decreasing amyloid deposits, the initiation of the first chemotherapy cycles led to the healing of the nephrotic syndrome and the resorption of the subretinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we focus on the management of ME and, in particular, on current data of studies and clinical trials about drugs that are under investigation or have already been evaluated in ME management. Although several diseases could lead to the development of ME (that is, DR 1 , RVO 2 , uveitis 3 , Irvine–Gass postoperative ME 18 , idiopathic macular telangiectasia type 1 and 2 19, 20 , perifoveal exudative vascular anomalous complex 21 , paclitaxel-induced maculopathy 22 , MEK inhibitor–associated maculopathy 23 , hypoproteinemia 24 , paracentral acute middle maculopathy 25 , and central serous chorioretinopathy 26 ), we will discuss the management of the major causes of ME, including DR, RVO, and uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…Although Izeedini et al [ 2 ] and Blige et al [ 3 ] have reported on cases of SRD that were associated with nephrotic syndrome, these patients only exhibited SRD around the central fovea. Thus, our present case is unique in that the SRD with intraretinal edema was extensive enough to cover the entire posterior pole.…”
Section: Discussionmentioning
confidence: 99%
“…The main symptoms of nephrotic syndrome, which is a renal disease, include severe proteinuria, hypoalbuminemia, edema, and dyslipidemia [ 1 ]. There have also been a few reports of serous retinal detachment (SRD) being associated with nephrotic syndrome [ 2 , 3 ]. The mechanism of SRD is said to involve intratissue fluid retention due to systemic fluid overload and hypoalbuminemia.…”
Section: Purposementioning
confidence: 99%